2005
DOI: 10.1128/jb.187.7.2297-2307.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Extracytoplasmic Function Protein Family Sigma Factor RpoE in Metal Resistance of Escherichia coli

Abstract: RpoE of Escherichia coli is a sigma factor of the extracytoplasmic function protein family and is required for the expression of proteins involved in maintaining the integrity of periplasmic and outer membrane components. RpoE of E. coli was needed for full resistance to Zn(II), Cd(II), and Cu(II). Promoter gene fusion and quantitative real time reverse transcription (RT)-PCR (qRT-PCR) assays demonstrated that expression of RpoE was induced by metals. Global gene expression profiles upon metal treatment of a ⌬… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 61 publications
(59 reference statements)
5
93
1
3
Order By: Relevance
“…Since there is increasing evidence to indicate that the periplasm is an important cellular compartment for copper homeostasis (Bagai et al, 2008;Egler et al, 2005;Hiniker et al, 2005;Macomber et al, 2007), elucidating the involvement of VcCot (VCA0261-0260) and Vc-CopG (VC2216) homologues in V. cholerae copper tolerance represented an interesting topic of study. The evaluation of the role of VC2215 and VC0974 genes in copper resistance was also interesting, since their original annotations were only based on sequence similarity.…”
Section: Resultsmentioning
confidence: 99%
“…Since there is increasing evidence to indicate that the periplasm is an important cellular compartment for copper homeostasis (Bagai et al, 2008;Egler et al, 2005;Hiniker et al, 2005;Macomber et al, 2007), elucidating the involvement of VcCot (VCA0261-0260) and Vc-CopG (VC2216) homologues in V. cholerae copper tolerance represented an interesting topic of study. The evaluation of the role of VC2215 and VC0974 genes in copper resistance was also interesting, since their original annotations were only based on sequence similarity.…”
Section: Resultsmentioning
confidence: 99%
“…26,27) Recently, DNA microarray assays have shown that zinc also stimulates the expression of genes among CpxAR regulon. 22,28,29) After a number of comparison of the sensitivity of the wild type and the cpxAR mutant to several metals, LiCl, NaCl, MgCl 2 , KCl, CaCl 2 , CrCl 3 , MnCl 2 , FeCl 2 , CoCl 2 , NiCl 2 , CuCl 2 , ZnCl 2 , RbCl, SrCl, CsCl, BaCl 2 , PbCl 4 , and AgNO 3 , we found that the sensitivity of the cpxRA-null mutant was For S1 nuclease analysis using these probes, the expected size of protected fragments (or transcripts) are: 81-nt for cpxP probe-1; 195-nt for ftnB probe-2; 147-nt for htrA probe-3; 170-nt for ppiA probe-4; 122-nt for spy probe-5; 148-nt (p1) and 234-nt (p2) for ybaJ probe-6; 90-nt for yccA probe-7; 119-nt for ycfS probe-8; 93-nt for ydeH probe-9; 180-nt for yebE probe-10; 160-nt for yihE probe-11; 109-nt for yobB probe-12; 133-nt for yqjA probe-13. highest against copper, followed by zinc (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Both pathways respond to environmental stresses and control expression of genes required for repairing of damaged proteins in the envelope (DiGiuseppe & Silhavy, 2003). Recently, it was found that activity of the disulfide isomerase DsbC (Hiniker et al, 2005) and increased expression of the porin OmpC (Egler et al, 2005) are required for copper tolerance. DsbC rearranges non-native disulfide bonds formed in periplasmic proteins damaged by copper; the underlying mechanism of OmpC function remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…During anaerobic growth, copper toxicity increases and another efflux system encoded by the cusCFBA operon is necessary for full copper tolerance (Grass & Rensing, 2001;Outten et al, 2001;Silver & Phung, 2005). In the presence of high copper concentrations, when the efflux complexes are overloaded, E. coli cells activate general stress responses governed by the sigma factor RpoE (Egler et al, 2005) and the twocomponent signal transduction system CpxRA (Kershaw et al, 2005;Yamamoto & Ishihama, 2005). Both pathways respond to environmental stresses and control expression of genes required for repairing of damaged proteins in the envelope (DiGiuseppe & Silhavy, 2003).…”
Section: Discussionmentioning
confidence: 99%